Sustainable Retirement Planning : Financial Attitudes, Financial Literacy, and Health Literacy (International Forum of Researchers and Lecturers, 2025)
This study examines the effects of financial attitudes, financial literacy, and health literacy on sustainable retirement planning among Indonesian retirees and pre-retirees aged 60 to 80 years. Employing a quantitative approach, data were collected from 249 respondents selected using stratified random sampling. Structural Equation Modeling (SEM) with SmartPLS was utilized to analyze the relationships between the variables. The results reveal that financial attitudes, financial literacy, and health literacy each have a positive and significant impact on sustainable retirement planning. Positive financial attitudes encourage proactive planning and long-term savings behavior, while higher financial literacy enables individuals to make informed decisions about investments, budgeting, and future financial security. Furthermore, improved health literacy supports better anticipation of medical needs and expenditures in retirement, further reinforcing financial preparedness and resilience. Additional analysis suggests that these three factors interact synergistically: individuals with strong financial and health literacy tend to maintain better lifestyle habits, engage in preventive healthcare, and allocate resources efficiently, leading to more sustainable retirement outcomes. Such preparedness not only reduces financial stress but also contributes to overall well-being and life satisfaction in later years. The findings of this study carry important implications for policymakers, financial institutions, healthcare providers, and educational stakeholders. Policymakers are encouraged to develop integrated programs that simultaneously promote financial and health literacy among the aging population. Financial institutions can leverage these insights to design products, advisory services, and retirement savings schemes tailored to the needs of older adults. Healthcare providers are urged to integrate financial planning awareness into health counseling for the elderly, while educational institutions should embed retirement, financial, and health literacy topics in adult education curricula. Collectively, these efforts are essential to empower older adults in achieving sustainable and secure retirement outcomes, ensuring that both financial stability and health considerations are addressed comprehensively.